The Effectiviness Of Applying KWL (Know, Want, Learn) Strategy On Reading Comprehension At SMP NEGERI 4 Pematangsiantar - Indra Jayanti; Yunita Karnelia Nasution (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
The aim of this research was to find out the effect of KWL strategy on the reading comprehension of the eight grade students at SMP NEGERI 4 PEMATANGSIANTA in the academic year of 2021/2022. This research was conducted on May 2022. This research was classified as a true-experimental study. It involved 64 students from two groups, class VIII5 (32 students) as the experimental group and VIII6 (32 students) as the control group. The experimental group was students taught using KWL strategy where as the control group was students taught using contial technique . The data were obtained by using pre-test and post-test. The data of the pre-test and post-test of both groups were analyzed by using descriptive and inferential statistic. (SPSS 22.0). The result of the research shows that the testing hypothesis of post-test score, it is found that tcount (8.63) > ttable (1.67) at the significance level a = 0.05 and degrees of freedom (df) = 63. H0 is rejected and Ha is accepted. So, it means that the KWL strategy effect significantly to improve students’ reading comprehension at the eight grade of SMP Negei 4 Pematangsiantar academic year of 2021/2022.